2009
DOI: 10.1021/la901830n
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Oxide Nanocrystals Stabilized by Alkylammonium Alkylcarbamates

Abstract: Nearly monodispersed, spherical ZnO nanocrystals were synthesized from the reaction of an amide precursor, [Zn(N(i)Bu(2))(2)](2), with hexylamine followed by reactions of the as-formed solution in a moist air flow. Extensive experiments were conducted to optimize the synthesis and to characterize the nanocrystals. The room temperature reactions led to 3.3-5.3 nm nanocrystals with the sizes increasing in direct proportion to the relative humidity. Purification afforded high yields of free-flowing nanocrystals t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 66 publications
1
40
0
Order By: Relevance
“…184 Gladfelter and co-workers also showed that moisture was the major reagent in the reaction of Zn(N i Bu2)2 under air. 189 The ZnO NP size increased as the humidity level was increased, while only amorphous products were formed under dry conditions. The presence or absence of O2 may still be important in the hydrolysis reaction: for example, the reaction of Fe(N(SiMe3)2)2 with water forms wüstite Fe1-yO NPs; 168,169 whilst under air the iron becomes oxidised, instead forming maghemite Fe2O3 NPs.…”
Section: Hydrolysis Routes To Metal Oxide Nanoparticlesmentioning
confidence: 97%
See 1 more Smart Citation
“…184 Gladfelter and co-workers also showed that moisture was the major reagent in the reaction of Zn(N i Bu2)2 under air. 189 The ZnO NP size increased as the humidity level was increased, while only amorphous products were formed under dry conditions. The presence or absence of O2 may still be important in the hydrolysis reaction: for example, the reaction of Fe(N(SiMe3)2)2 with water forms wüstite Fe1-yO NPs; 168,169 whilst under air the iron becomes oxidised, instead forming maghemite Fe2O3 NPs.…”
Section: Hydrolysis Routes To Metal Oxide Nanoparticlesmentioning
confidence: 97%
“…Hydrolysis of reactive metal precursors can take place under air, where both water vapour and O2 can act as the oxygen source (vide infra). Several studies have indicated that water vapour is typically the key reagent under these conditions, 184,189 however, the presence of oxygen may affect the products, especially where an oxidisable metal precursor is used (e.g. Fe(N(SiMe3)2)2 or Ni(4-C8H12)2).…”
Section: Hydrolysis Routes To Metal Oxide Nanoparticlesmentioning
confidence: 99%
“…The same conclusion species. 18,26,30,31,32,33,34 The N 1s peaks have been fitted using these components and a progressive increment of the -NH 3 + /-NH 2 ratio is observed along the ripening process (see Table S1 and Figure S2 in supporting information). Furthermore, carbamation seems to be constant along the ODA/mica SAM exposition to air, as indicated by the evolution of the 400.2 eV component in Figure 3.…”
Section: 21mentioning
confidence: 99%
“…It is known that carbamates or carbamic acids could be formed in ambient or supercritical conditions from the reaction between amines and CO 2 . The carbamates were reported as efficient stabilizers which not only could improve the stability and uniformity of the nanoparticles but also could reduce the size as well as manipulate the shape of the nanoparticles . On the other hand, the addition of CO 2 would lead to a volume expansion of the solvent, thus forming a CO 2 ‐expanded liquid (CXL) system .…”
Section: Resultsmentioning
confidence: 99%